Effects of ethanolic extracts from Tinospora crispa (L) Hook.f. & Thomson and Andrographis paniculata (Burm.f.) Nees on the in vitro lytic cycle of Toxoplasma gondii infection - Abdullahi, Sharif Alhassan (2019)
Infection with Toxoplasma gondii remains widespread because, water, soil, and food, serve as major carriers of the sporulated oocyst. The infection is poorly controlled due to the lack of a potent vaccine against the parasite, and the current medication presents with severe side effects on the host, less efficacy on the parasite and accompanied by the potential development of resistance. There is, therefore, the need to discover and develop better and safer drugs, especially from natural herbs to combat toxoplasmosis. This study, therefore, evaluated the in vitro activities of ethanolic extracts of Andrographis paniculata (EEAP) and Tinospora crispa (EETC) on protein kinases involved in the lytic cycle of T. gondii infection. The EEAP and EETC were obtained through the maceration of dried leaves and stem powder respectively. Both EEAP and EETC were subjected to qualitative and quantitative screening for the detection and estimation of the major phytochemicals. Vero cells infected with the RH strain of T. gondii were used to evaluate the cytotoxicity and antiparasitic potentials of the EEAP, EETC, alkaloid, and clindamycin through MTT assay. Microscopy was used to assess on the effects of the EEAP, EETC, and clindamycin on cell invasion and intracellular replication of the tachyzoite on treated infected Vero cells at 24 h and 48 h using 4 h and 24 h post-infection models. Using the same treatment models for both EEAP and EETC, gene expression profiling of the T. gondii protein kinase genes was determined through quantitative real-time PCR (RT-qPCR) after 24 h of treatment. The expression of microneme protein was determined through western blot technique. The EEAP and EETC were found to contain alkaloid, flavonoids, tannins, terpenoids and glycosides. The EEAP, EETC, and clindamycin were safe to the host cells while alkaloid presented with moderate cytotoxicity. The EEAP and EETC showed good anti-parasitic activities against T. gondii than clindamycin and veratrine alkaloid. Microscopic assessment revealed high %inhibition of infection index and intracellular replication by the EETC and EEAP in both 24 hour and 48 h treatment exposure than the clindamycin in both infection models. The RT-qPCR revealed downregulation of most protein kinase genes after treatment with EEAP and EETC in 4 h and 24 h treatment models. The TgCDPK1, TgPKG, TgCDPK7, TgMIC1, TgMIC2, and TgAMA1 genes that participate in the lytic cycle of T. gondii infection were downregulated in all treatment conditions. The TgCDPK3 was downregulated in 4 h post-infection treatment but upregulated in EEAP treated group in 24 h postinfection treatment group but is not statistically significant from the control group (P > 0.05). The TgCDPK6 gene was found to be downregulated, though not significant from control, in all treatment conditions except for EEAP treatment where it was significantly upregulated in 24 h post-infection treatment model (P<0.001). The expressions of the TgMIC1 and TgMIC2 proteins were observed to have decreased in both 4 h and 24 h post-infection treatment models. The expressions of TgMIC2 were significantly different from the control. This study showed that the EEAP and EETC contain promising drug candidates effective against T. gondii and safe to the host cells and can potentially be used in the future for the development of a potent antitoxoplasma compound that can target the protein kinase genes involved in the lytic cycle of the T. gondii parasite to prevent disease progression.